2012
DOI: 10.1002/mame.201200253
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of a Polyamide 6/Montmorillonite Nanocomposite at Rapid Cooling

Abstract: The crystallization behavior of a polyamide 6/organo‐modified montmorillonite (PA 6/OMMT) nanocomposite has been investigated by scanning chip calorimetry and wide‐angle X‐ray scattering, with emphasis placed on the evaluation of the effect of supercooling/cooling rate on the crystal/mesophase polymorphism of the PA 6 matrix. Presence of OMMT has negligible effect on the kinetics of formation of α‐crystals of PA 6 at low cooling rate while there is observed enhanced nucleation of γ‐mesophase on fast cooling. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…It was found for a specific system containing 5 m% organomodified MMT (OMMT) that the PA 11 crystallization temperature was only increased on cooling faster than about 1 K s -1 and that the critical cooling rate to suppress crystallization of PA 11 was significantly increased. Similar observations have been reported for nanocomposites based on PA 6 [32].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was found for a specific system containing 5 m% organomodified MMT (OMMT) that the PA 11 crystallization temperature was only increased on cooling faster than about 1 K s -1 and that the critical cooling rate to suppress crystallization of PA 11 was significantly increased. Similar observations have been reported for nanocomposites based on PA 6 [32].…”
Section: Introductionsupporting
confidence: 90%
“…For many polymers including polypropylene [18][19][20], polyoxymethylene [21], poly(ethylene terephthalate) [22], poly(butylene terephthalate) [23], poly(butene-1) [24], but in particular polyamides [25][26][27][28][29][30][31][32][33][34], it has been shown that addition of nanofillers often enhance crystallization and even support the formation of specific crystal polymorphs. In fewer cases, however, a retardation of the crystallization process has also been reported, likely due to an immobilization of polymer chain segments at the polymer/nanofiller interface [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…This effect was explained by an immobilized polymer layer in the vicinity of the layered silicates (Rigid Amorphous Fraction, RAF). For the PCL MWCNT composite the interaction between the polymer and the MWCNTs seems not to result in the formation of a significant RAF as it was also seen for other polymers [172,173].…”
Section: Identification Of Different Nuclei Populationsmentioning
confidence: 58%
“…Particularly it is important to know how nuclei or small crystals influence cold-crystallization at a given temperature [161,172,173]. Therefore heating experiments at the heating rate of 18,000 K/s for PCL after cooling with 100,000 K/s and annealing at three selected temperatures were collected.…”
Section: Identification Of Different Nuclei Populationsmentioning
confidence: 99%
“…Furthermore, modified cooling conditions affect the development of internal structures of the part. Thus, an increased cooling rate favours the formation of orientations and residual stresses [12,13] as well as an inhomogeneous morphology [14] associated with a modified crystalline structure [15][16][17][18][19][20].…”
mentioning
confidence: 99%